2023
DOI: 10.1039/d2cc06007h
|View full text |Cite
|
Sign up to set email alerts
|

Supermolecule-assisted synthesis of perovskite nanorods with high PLQY for standard blue emission

Abstract: We fabricated CsPbBr3 nanorods with standard blue emission (462 nm) and a high PLQY of ~90% with the assistance of supermolecule. The β-CD works as co-ligands and confines isotropic growth...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The PL decay was fitted as bi-exponential PL decay kinetics. The relatively long lifetimes ( τ 2 ) of 20.63, 36.52, and 29.78 ns suggested strong exciton radiative recombination at room temperature, 35–39 which demonstrated excellent optical properties of CsPbBr 3 NRs. 40…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The PL decay was fitted as bi-exponential PL decay kinetics. The relatively long lifetimes ( τ 2 ) of 20.63, 36.52, and 29.78 ns suggested strong exciton radiative recombination at room temperature, 35–39 which demonstrated excellent optical properties of CsPbBr 3 NRs. 40…”
Section: Resultsmentioning
confidence: 98%
“…The PL decay was fitted as bi-exponential PL decay kinetics. The relatively long lifetimes (t 2 ) of 20.63, 36.52, and 29.78 ns suggested strong exciton radiative recombination at room temperature, [35][36][37][38][39] which demonstrated excellent optical properties of CsPbBr 3 NRs. 40 In three-dimensional blue CsPbBr 3 perovskite materials, the main charge carriers are present in the form of free charges, and the exciton binding energy is small, further limiting the light emission efficiency of the devices.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous studies have demonstrated that β-CD can also help to regulate perovskite growth and passivate possible defects to enhance device efficiency and moisture-resistance properties due to its host-guest interaction with the perovskite (FA + or MA + ) and hydrophobic nature. 36–40 As a result, both high efficiency (>23%) and good stability are obtained in PSCs with β-CD. The resulting PSCs retain ∼90% of the highest efficiency after MPP tracking for 1000 hours at 25 °C based on the ISOS-L-1 protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their potential, the application of CDs in HG complexes with metal halide perovskites in solar cells and LEDs has seen limited use. 11,44,[51][52][53][54][55] Previous studies highlight b-CD's pivotal role in regulating growth, improving device efficiency, and enhancing moisture resistance. Notable applications include stable MAPbBr 3 /b-CD nanodots for diverse use, 44 and crucial role of b-CD in achieving standard blue emission and high photoluminescence quantum yield in CsPbBr 3 nanorods, ensuring stability against moisture and oxygen.…”
Section: Introductionmentioning
confidence: 99%